Rancang Bangun SSPD (The System of Solar-Powered Drier) untuk Peningkatan Produksi Usaha Ikan Asin Kerupuk Desa Kuala Geulumpang - Wan Alamsyah; Asmadi Suria; Rachmad Almi Putra (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2019)
This service activity aims to design fish dryers to help with the problems of the drying process in the rain, packaging repairs, and market expansion. This activity is conducted from September to October 2018 in collaboration with Ratama KUB. The results achieved were the design of a device called The Solar Powered Drier System, which has a capacity of 216 liters and a temperature of 50-70 degrees Celsius, and a market network has built with Arsala department store. Activities. The existence of SSPD equipment for cracker salted fish drying machines, does not provide a significant increase in production because the engine capacity is tiny. Packaging repairs can improve marketing in the surrounding area, namely East Aceh and the city of Langsa.